OZONE LAYER DEPLETION CAUSES, HUMAN AND ENVIRONMENTAL IMPACTS, AND MITIGATION STRATEGIES – A COMPREHENSIVE REVIEW - Mohammad Pazir Hakimi; Mohammad Yaqoob Sarfaraz; Nazir Jan Sadiqi (CV. Radja Publika, 2025)
The depletion of ozone, which accelerates the emergence of ultraviolet (UV) radiation and other solar rays, has become one of the biggest threats to the world in recent years. This review article investigates the causes of depletion of the ozone layer and its effects on human health. This study provides a general overview of the ozone layer, highlighting its significance in preserving life on Earth and the scientific rationale behind its deterioration. It examines a number of human factors, such as industrial emissions, agricultural practices, and the use of certain chemicals that contribute to the depletion of the ozone layer. The effects of ozone layer depletion on human health, including a higher risk of skin cancer, cataracts, and a compromised immune system, are also covered in this article. It also identifies initiatives taken to solve this problem through international accords, such as the Montreal Protocol, and offers suggestions for future analysis and policy measures to reduce ozone layer loss and safeguard human health. Overall, this review article emphasizes the necessity for collaborative efforts to protect human well-being, while providing an insightful understanding of the causes and effects of ozone layer depletion.